RESILIENCE MANAGEMENT OF INDONESIAN TOURISM VILLAGES TOWARDS SHOCK OR CRISIS - Hariyanto; Agita Arrasy Asthu (UPT Publikasi Ilmiah UNISBA, 2025)
This study explores the resilience of tourism villages in Indonesia in the face of shocks or crises, focusing on five Super Priority Tourism Destinations (DPSP): Labuan Bajo, Mandalika, Borobudur, Likupang, and Lake Toba. Using a qualitative approach through literature study, this study identifies the impact of the crisis on various dimensions of tourism village development, including products, marketing, institutions, investment, adaptation, and needs. The results show that despite a decrease in the overall dimension score of 28.14%, tourism villages show a relatively high level of resilience compared to other tourism destinations. This is due to the characteristics of homogeneous communities and strong social ties. Strategies to accelerate recovery include effective communication, normalization of activities, structured recovery planning, and collaboration between stakeholders. This study emphasizes the importance of adaptive and collaborative governance in building tourism village resilience to various crises in the future.